Avifaunal Diversity of Ukkadam Lake in Coimbatore District of Tamilnadu (India) - Nandha Kumar, C.; Revathi, R.; Jaisankar, I.; Baranidharan, K.; Durai Rasu, P. (Indian Forester, 2014)
Birds are excellent indicators of water quality and measures of biodiversity. The study on bird diversity was conducted during November 2012 to March 2013 at Ukkadam Lake, Coimbatore, Tamil Nadu. Total of 48 avifaunal species belonging to 20 families were recorded in the study area. The result showed that only one species was rare, one species was winter visitor, two species belong to nearly threatened category, two species critically endangered and forty species were under the least concerned category. Species diversity and species richness showed that more bird diversity occurred in the month of March followed by January and February and least in the month of November. Highest bird population was observed in the monthJanuary and February